Ausentes, vingativas, irreverentes, infantis: as personagens femininas na obra de Quentin Tarantino - SILVA, Carolina de Oliveira (2017)
This research aims to understand the female characters in the work of the American filmmaker Quentin Tarantino, starting from a type of film extremely influential in the constitution of its style: the exploitation of the decades of 1950-1970, in its challenging nature of integration between conventions and ruptures. The idea is to show, through film analysis, how these characters are characterized and what makes them relevant and distinct whitin the narratives worked, contemplating a division that cuts the main characteristics used in its construction. Tarantino’s approach is admitted by these subversive and dubious films about their representations and serves as a starting point for discussions about contemporary feminist concerns and post-feminism itself. In this sense, four approaches to these characters are possible: absent, vindictive, irreverent and infantile women, thus allowing to reflect on the transformation of the female figure throughout the work of Quentin Tarantino.